1994
DOI: 10.1111/j.1365-2133.1994.tb13119.x
|View full text |Cite
|
Sign up to set email alerts
|

A fatal case of scleredema of Buschke

Abstract: Scleredema of Buschke is a rare disorder characterized by the development of areas of skin induration which usually resolve spontaneously. It is occasionally associated with a benign gammopathy, and rarely with myelomatosis. We describe a 60-year-old woman with extensive skin changes, who developed IgA myeloma. Unusually, her skin disease did not respond to conventional myeloma therapy. Death occurred as a consequence of the progressive skin disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 5 publications
0
33
0
3
Order By: Relevance
“…8 Rarely is scleredema fatal. 9 Three types of scleredema have been described. The classic type, described by Buschke, follows a febrile illness, and symptoms usually resolve completely.…”
Section: Commentmentioning
confidence: 99%
“…8 Rarely is scleredema fatal. 9 Three types of scleredema have been described. The classic type, described by Buschke, follows a febrile illness, and symptoms usually resolve completely.…”
Section: Commentmentioning
confidence: 99%
“…Scleredema is rarely fatal though some cases have been described in literature [21,28]. The classic natural history is a spontaneous resolution in < 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…The potential chronicity and severity of the disorder should not be underestimated, as there have been at least two deaths due to scleredema. 15,16 Histologically, scleredema shows a normal epidermis but the dermis may be three times the normal thickness with swelling and splitting of the dermal collagen bundles and variable deposition of the mucin in the dermis, histochemical analysis have shown that the amount of glycosaminoglycans and collagenase increased in the affected skin.…”
Section: Discussionmentioning
confidence: 99%